The New Indonesian Company Law - PULLE, Austin Ignatius (Institutional Knowledge at Singapore Management University, 1996)
Objectives of legislation in force March 1996 and provisions on formation, share capital, minority protection, shareholders meetings, company management, judicial investigations and liquidation.